The Predictive Value of Serum Inflammatory Factors High-sensitivity C-reactive Protein Combined with High Level of Lipoprotein-associated Phospholipase A2 for the Onset of Ischemic Stroke: serum Lp-PLA2, MPO, serum ferritin in Ischemic Stroke - Zuo, Yaojin (Journal of Medical Biochemistry, 2025)
Objective: the aim of this article was to carried out an exploration of the predictive value of serum high-sensitivity C-reactive protein (hs-CRP) plus high levels of lipoprotein-associated phospholipase A2 (Lp-PLA2) for the onset of ischemic stroke (IS).Material and Method: 526 IS patients were selected as the experimental group (EG). During the same period, 463 healthy individuals served as the control group (CG). The levels of Lp-PLA2, myeloperoxidase (MPO), total cholesterol (CHO), low-density lipoprotein cholesterol (LDL-C), triglyceride (TG), hs-CRP, and serum ferritin (SF) in the serum of subjects were compared. The predictive efficacy of combination of two for the onset of IS was assessed.Result: the levels of Lp-PLA2, MPO, CHO, LDL, TG, hs-CRP, and SF in patients with IS were all markedly higher as against the CG (P
Keywords: IS; hs-CRP, Lp-PLA2; inflammation factors; predictive value